ANALISIS DAYA SAING POTENSI UNGGULAN KABUPATEN SLEMAN - Febri Nugroho Mujiraharjo (Faculty of Industrial Technology Universitas Islam Indonesia, 2017)
In the current era of regional autonomy, regional development will be more complex. The existence of the gap between the region and the development of globalization resulted in competition between regions become increasingly tight. Sleman Regency has superior sectors in the construction, transportation and warehousing sector, real estate services and services business, which is influenced by sleman regency which is adjacent to Yogyakarta City so that it can form urban agglomeration area. Sleman Regency urban agglomeration region is a sleman district area as center of education, office, hotel and National Peace Center in accordance with RT / RW of Sleman district.